Incidencia de los factores de riesgo del embarazo en adolescentes y su relación con la anemia ferropénica en pacientes atendidas en el Subcentro de salud siete de octubre, del cantón Quevedo, periodo de julio a diciembre del 2014 - Franco Cedeño, Yeny Victoria (2015)
This research was conducted in the health sub center Seven October the same that is located in the Siete de Octubre, Ninth Street and the "H" parish, which was established as a goal: to identify risk factors with the highest incidence Teen pregnancy-related iron deficiency anemia in patients treated at the Health Subcentro Seven October, Quevedo Canton, period July to December 2014. The research was used to obtain bibliographic information books, basis and other data for the fieldwork was necessary to apply surveys and interviews, then the descriptive, deductive, inductive methods were used, and also to complete the research and translating the results was due to use statistics and then proceed to the tabulation , description and analysis. Finally he reached the following conclusions, it was determined that 58% of adolescents had their first sexual relationship between 12 and 15 years of age who are not ready to become mothers; 48% said that during pregnancy are not properly fed. It was also determined that have not led monthly control; during the stage of pregnancy have had symptoms such as headaches, edema, poor appetite, sleepy, tiredness and fatigue; although intra and extra mural talks about preventing sexually transmitted diseases and even in the SCS are promoted, and existing dispensers male protectors occurred in young people greater license to have sex freely. Besides the 48% he mentioned receiving no sex education by their parents or at school. Well, most teenagers live in extreme poverty, many of them single mothers living at home with their parents. Therefore, it is necessary and indispensable to propose a training plan for preventing risk factors in pregnant adolescents seen at the Health Subcentro Seven of October. Key words: Risk factors , pregnancy, adolescents , iron-deficiency anemia